Examination of science learning equity by argumentation ınstruction between students having different socio-economic status and attending different achievement level schools - Acar, Ömer (Journal of Turkish Science Education, 2016)
We investigated if argumentation instruction provides equal science learning opportunities to students who have different socio-economic status (SES) and attend different achievement level schools. We selected a disadvantaged school and an advantaged school for this aim. 46 low-SES 8th graders in the disadvantaged school formed the experimental group. 35 low-SES 8th graders in the disadvantaged school formed the control group and 29 high-SES 8th graders in the advantaged school formed the comparison group. While experimental group received argumentation instruction on science topics during one semester, control and comparison groups did not. We compared group performances on conceptual knowledge, utility value of science, beliefs on theory and data, and views on student-centered teaching. Results showed that students of experimental and comparison groups outperformed students of control group on all measures after instruction. In addition, no difference was found between experimental and comparison group after instruction except from beliefs on theory and data measure.